Analisis Kinerja Keuangan Sebagai Dasar Pengambilan Keputusan Pada PT. Sinar Makmur Palembang - Frans Habrizons (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2019)
PT. Sinar Makmur Palembang is a company engaged in the trading of goods and services that must be able to properly carry out financial policies to carry out company operations. companies acquired over several periods with the help of financial statement analysis tools, namely vertical and horizontal analysis. Research results obtained from data analysis that have been carried out on the financial statements of profit and loss and balance sheet for 4 periods, namely from 2013-2016, based on horizontal analysis on the income statement of PT. Sinar Makmur Palembang, it can be seen that there is fluctuation in the company's operating income. Information on this fluctuation is important for management in the decision to predict the company's capacity to produce existing resources, while in the profit and loss statement and balance sheet of PT. Sinar Makmur Palembang as a whole tends not to be optimal where there are still fluctuating estimates.